The Only Child - Julius Ilciukas; Petter Lundborg; Erik Plug; Astrid Würtz Rasmussen (Institute of Labor Economics (IZA), 2025)
We estimate the impact of having siblings on school outcomes of first-born children. By leveraging exogenous variation in first and later IVF treatments, we construct an improved instrumental variable estimator that tackles exclusion violations and identifies causal effects for compliers and always takers with siblings from later treatments. With nationwide school surveys linked to administrative records, we find that first-born children with and without siblings perform equally well on nationwide reading and math tests, are equally conscientious, agreeable, and emotionally stable, and report the same levels of school well-being. We conclude that the cognitive and non-cognitive outcomes of school-aged first-born children neither benefit nor suffer much from having siblings.
Keywords: I21; J13; C26; 330; cognitive and non-cognitive development; siblings